1997
DOI: 10.1097/00004836-199700001-00018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Cyclooxygenase-2 Gene in Gastric Epithelium

Abstract: This study examined the mRNA level of cyclooxygenase-2 (cox-2) in a rat gastric mucosal cell line after growth stimulation in vitro and in rat gastric mucosa before and after acid-induced injury in vivo. RGMI cells were stimulated with fetal calf serum in the in vitro study. Thereafter, the cox-2 mRNA level was examined by Northern analysis. Effects of NS-398, a specific inhibitor of cox-2, and indomethacin on prostaglandin production and cell proliferation were examined in RGM1 cells. In the in vivo study, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 28 publications
4
30
0
Order By: Relevance
“…An initial study by Seibert et al (1997) suggested that COX-1 mRNA was readily detectable in all normal tissue examined, especially in stomach and others, but that levels of COX-2 mRNA were substantially lower, with the exception of the brain. Several studies, including the present study, have shown that unstimulated gastric mucosa express a lower level of COX-2, whereas gastric mucosal epithelium expresses this isoform after various stimuli (Sawaoka et al, 1997;Sun et al, 2000). In the present study, lansoprazole enhanced the expression of mitogen-inducible COX-2, but not that of constitutive COX-1 in rat gastric mucosa.…”
Section: Lansoprazole Up-regulates Cox-2supporting
confidence: 53%
See 1 more Smart Citation
“…An initial study by Seibert et al (1997) suggested that COX-1 mRNA was readily detectable in all normal tissue examined, especially in stomach and others, but that levels of COX-2 mRNA were substantially lower, with the exception of the brain. Several studies, including the present study, have shown that unstimulated gastric mucosa express a lower level of COX-2, whereas gastric mucosal epithelium expresses this isoform after various stimuli (Sawaoka et al, 1997;Sun et al, 2000). In the present study, lansoprazole enhanced the expression of mitogen-inducible COX-2, but not that of constitutive COX-1 in rat gastric mucosa.…”
Section: Lansoprazole Up-regulates Cox-2supporting
confidence: 53%
“…The mitogen-inducible isoform (COX-2) is minimally expressed in normal stomach Kargman et al, 1996). COX-2 expression is enhanced, however, in gastric epithelial cells after growth stimulation in vitro and in gastric epithelium after acid-induced damage in vivo Sawaoka et al, 1997). We recently demonstrated that COX-2 protein is overexpressed during the healing of gastric lesions and a COX-2-specific inhibitor delays healing in the rat, suggesting an important role for this isozyme in gastric ulcer healing (Sun et al, 2000).…”
mentioning
confidence: 99%
“…41) Hydrochloric acid is a necrotic agent that induces wide hemorrhagic bands in the gastric corpus 60 min after HCl administration. 42) Pretreatment with AG 50 min before HCl/ethanol solution increased the severity of lesions in a dose-dependent manner by 64% (250 mg/kg) and 46% (500 mg/kg), in relation to mice treated with vehicle (Table 3). We also observed that the lowest dose of AG showed the highest activity.…”
Section: Resultsmentioning
confidence: 95%
“…Although COX-2 expression in the healthy stomach is low and expression around a site of ulceration is considerably higher, it should be noted that rapid induction of COX-2 can occur, even in response to quite subtle mucosal irritation. A further functional role for COX-2 in mediating gastric epithelial proliferation has been demonstrated by Sawaoka et al (1997), whereas Nakatsugi et a1. (1996) have provided evidence that COX-2 contributes to mucosal defense in a rat model of stress ulcer.…”
Section: B Selective Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 95%